A Review of Abductor Tendon Tears: The Hidden Lesion of the Hip. Issue 12 (22nd December 2022) - Dove, James H.; Lemme, Nicholas J.; Modest, Jacob M.; Talley-Bruns, Rachel C.; Tabaddor, Ramin R.; Fadale, Paul D.
Abstract : » Greater trochanteric pain syndrome consists of a group of associated conditions involving the lateral hip that can be debilitating to patients, mostly women between ages 40 and 60 years. » Abductor tendon tears are becoming a more recognized cause of lateral hip pain in patients without hip osteoarthritis. » Diagnosis of this condition is critical to patient care because misdiagnosis often leads to unnecessary prolonged pain and even unnecessary procedures that address different pathologies. » Treatment strategies consists of nonoperative modalities such as nonsteroidal anti-inflammatory medications, corticosteroid injections, and physical therapy, but for refractory cases, surgical techniques including repair, augmentation, and reconstruction have been well-described in the literature providing patients with acceptable outcomes.